2014
DOI: 10.1109/tip.2014.2316377
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Scattered Data Interpolation for Pushbroom Image Rectification

Abstract: Abstract-This article deals with fast and accurate visualization of pushbroom image data from airborne and spaceborne platforms. A pushbroom sensor acquires images in a linescanning fashion, and this results in scattered input data that needs to be resampled onto a uniform grid for geometrically correct visualization. To this end, we model the anisotropic spatial dependence structure caused by the acquisition process. Several methods for scattered data interpolation are then adapted to handle the induced aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Normal Kriging works very well in interpolation (e.g. gabean et al, 2010)), image rectification (Ringaby et al, 2014) and related applications, however we found that it underperformed in our application and was therefore omitted. Even Kriging refinement improved the results only marginally.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Normal Kriging works very well in interpolation (e.g. gabean et al, 2010)), image rectification (Ringaby et al, 2014) and related applications, however we found that it underperformed in our application and was therefore omitted. Even Kriging refinement improved the results only marginally.…”
Section: Resultsmentioning
confidence: 73%
“…To counter these effects, we introduce an adaptive splat kernel, adjusted to the local density of projected points. This is a generalization of ideas found in (Ringaby et al, 2014), where the shape of the region is defined for the application of an aircraftmounted push-broom camera. Here we generalize this by instead estimating the shape from neighboring projected points: For each candidate point, we calculate the distances between its projected position in the output image and the projected positions of its eight nearest neighbors in the input image.…”
Section: Global Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…The inverse interpolation scheme guarantees that each point in the output grid is assigned a predicted value [44]. We assumed that the k-means clustering can accurately stratify the fragmented landscape.…”
Section: Statistical Upscaling Of Pft Distribution On the Landscapementioning
confidence: 99%